Presentation of disseminated neuroblastoma mimicking Bell’s palsy: a case report - Shamaali Gunawardana; Geerthana Jogaprajahpan; Kavinda Dayasiri (Journal of Medical Case Reports)
Abstract Background Neuroblastoma is an embryological malignancy of neural crest cells that may have diverse presentations owing to direct effects, metastases, or paraneoplastic syndromes. Facial nerve palsy is an extremely rare presentation of neuroblastoma. Case presentation A previously healthy 1-year-and-10-month-old Sinhalese girl presented with difficulty in closing her left eye for 2 weeks, preceded by deviation of her mouth to opposite side. Initial physical examination was normal, apart from left lower-motor-type facial nerve palsy. Initial laboratory investigations were also normal. A tentative diagnosis of Bell’s palsy was made. However, magnetic resonance imaging of the brain was performed owing to the incidental detection of a painless bulge in the left zygomatic region with overlying skin bruising, in the absence of any preceding trauma. Magnetic resonance imaging of the brain revealed a soft-tissue mass in the left lateral orbital wall, extending to the body of the sphenoid and bulging into the left anterior fossa. Contrast-enhanced computed tomography of the abdomen, performed subsequently, showed an intra-abdominal large paravertebral soft-tissue mass. Histology of the abdominal mass confirmed poorly differentiated neuroblastoma. Conclusion Facial nerve palsy is well recognized to have a myriad of underlying etiologies, including hematological malignancies, solid tumors, and paraneoplastic syndromes. However, its timely diagnosis is often challenging in the absence of other supportive clinical features. These children need careful and thorough evaluation for malignancies before commencing steroids, especially when underlying malignancy is likely.